Pengaruh Promosi dan Kualitas Produk Terhadap Minat Beli Kerudung Rabbani (Studi Kasus Pada Pondok Pesantren Putri Walisongo Cukir Jombang) - Nur Aini; Lik Anah (BIMA : Journal of Business and Innovation Management, 2019)
The purposes of this research are to know: 1. The influence of promotion toward the buyers’ interest, 2. Whether or not the product quality influences the buyers’ interest and 3. Whether or not promotion and the product quality influence the buyers’ interest. This is an explanatory research using a quantitative approach. There are three variables in this research, namely promotion (X1), the product quality (X2) andthe buyers’ interest (Y). The data was got by administering the offline questionnairs to the university students staying at Islamic Boarding School of Girl of Walisongo Cukir Jombang, in which their ages were 18 years old up to 23 years old. The sample used in this research was 109 respondents. The sampling used was the purposive sampling. The data was analyzed by using multiple linear regression analysis. The results of the research show that the variable of promotuion influences the process of decision making in buying. Then, variable of the quality of the product influences the process of decision making in buying. Both the promotion and the product quality influence the buyers’ interest. Based on the result of this study, it is suggested that Rabbanishould be able to defend and increase their promotion as well as improve their product quality because the variables of promotion and the product quality have the dominant influence toward the buyers’ interest. Keywords: Promotion; Product Quality; Buyers’ Interest The purposes of this research are to know: 1. The influence of promotion toward the buyers’ interest, 2. Whether or not the product quality influences the buyers’ interest and 3. Whether or not promotion and the product quality influence the buyers’ interest. This is an explanatory research using a quantitative approach. There are three variables in this research, namely promotion (X1), the product quality (X2) andthe buyers’ interest (Y). The data was got by administering the offline questionnairs to the university students staying at Islamic Boarding School of Girl of Walisongo Cukir Jombang, in which their ages were 18 years old up to 23 years old. The sample used in this research was 109 respondents. The sampling used was the purposive sampling. The data was analyzed by using multiple linear regression analysis. The results of the research show that the variable of promotuion influences the process of decision making in buying. Then, variable of the quality of the product influences the process of decision making in buying. Both the promotion and the product quality influence the buyers’ interest. Based on the result of this study, it is suggested that Rabbanishould be able to defend and increase their promotion as well as improve their product quality because the variables of promotion and the product quality have the dominant influence toward the buyers’ interest.